Aktivitas Antioksidan dan Profil Sensori Minuman Sari Kacang Merah (Phaseolus vulgaris L.) dengan Penambahan Ekstrak Jahe Merah - Ahmad Pandiansyah; Nurul Asiah; Kurnia Ramadhan; Ardiansyah Ardiansyah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
The diversification and product development of kidney bean and ginger products have not yet been fully explored, especially in relation to antioxidant activity and sensory profiles. This study aims to evaluate the antioxidant activity, total phenolic compounds (TPC), sensory profile, and consumer acceptance of a kidney bean drink with added red ginger extract. Three variations of the kidney bean drink were tested, each containing different concentrations of red ginger extract: 0, 4, and 8%. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, while TPC was determined using the Folin Ciocalteu method. Sensory analysis was conducted using the free choice profiling (FCP) method, with results analyzed through generalized procrustes analysis (GPA) to identify the sensory characteristics of the samples. Additionally, a hedonic test was used to assess the level of panelists' preference for each sample. The results showed that the addition of red ginger extract significantly affected (p<0.05) the antioxidant activity, TPC, sensory profile, and consumer acceptance of the kidney bean drink. Antioxidant activity demonstrated a substantial percentage of DPPH inhibition, ranging from 38.01 to 58.00%. TPC content values ranged from 0.91 to 1.80 mg GAE/g. The kidney bean drink exhibited various sensory attributes, including brown color, ginger aroma, caramel aroma, sweet taste, spicy taste, beany taste, liquid mouthfeel, creamy mouthfeel, spicy aftertaste, and beany aftertaste. The hedonic test results showed that panelists' preferences ranged from neutral to somewhat liking, with scores between 4.00 and 5.10.